2017
DOI: 10.1159/000480331
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Effect of Azaspiracid-1 Over the Human Intestinal Barrier

Abstract: Background: Azaspiracids (AZAs) are marine biotoxins produced by the dinoflagellates genera Azadinium and Amphidoma. These toxins cause azaspiracid poisoning (AZP), characterized by severe gastrointestinal illness in humans after the consumption of bivalve molluscs contaminated with AZAs. The main aim of the present study was to examine the consequences of human exposure to AZA1 by the study of absorption and effects of the toxin on Caco-2 cells, a reliable model of the human intestine. Methods: The ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…On the contrary, AZAs caused accumulation of fat droplets in mice liver [30]. An involvement of autophagy can be hypothesized in digestive glands accumulating A. dexteroporum -AZAs, consistently with the regulation of neutral lipid metabolism upon food restriction [66] and the observation of autophagosomes in the cytoplasm of AZA-1 treated intestinal cells [29]. Autophagy has been also associated with destabilization of lysosomal membranes and accumulation of lipofuscin in the lysosomes [68,69], which were both observed in the digestive gland of A. dexteroporum -exposed mussels.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…On the contrary, AZAs caused accumulation of fat droplets in mice liver [30]. An involvement of autophagy can be hypothesized in digestive glands accumulating A. dexteroporum -AZAs, consistently with the regulation of neutral lipid metabolism upon food restriction [66] and the observation of autophagosomes in the cytoplasm of AZA-1 treated intestinal cells [29]. Autophagy has been also associated with destabilization of lysosomal membranes and accumulation of lipofuscin in the lysosomes [68,69], which were both observed in the digestive gland of A. dexteroporum -exposed mussels.…”
Section: Discussionmentioning
confidence: 94%
“…ovata , Gymnodinium catenatum and Prorocentrum lima ) [45,58,61,62,63], and in mice, where AZAs caused erosion and shortening of intestinal villi [30,50]. However, a direct role of AZAs on digestive tissue morphology is still controversial, since no structural damage to intestinal cells was demonstrated after in vitro treatment with these biotoxins [29]. Since the atrophy of digestive tubules is a typical symptom of reduced feeding or starvation in bivalves [61], a similar mechanism may be hypothesised in the mussels exposed to A. dexteroporum , as often observed in bivalves exposed to toxic microalgae [35,64,65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no pharmacokinetics data in humans. Intestinal absorption has been demonstrated in vivo in mice and in vitro in human intestinal cell cultures [ 197 , 198 ]. AZA1 is widely distributed after absorption, being detected in several organs including spleen, kidney, lung, heart and liver, and only trace amounts in the brain [ 198 ].…”
Section: Azaspiracidsmentioning
confidence: 99%
“…Figure 1.3 Chemical structures of AZA toxins 1, 2 and 3 (Twiner et al, 2012a) AZA consumption results in increased permeability of the intestine, leading to fluid accumulation in the small intestine and diarrhoea. The mode of action of AZA is unclear, studies conducted on Caco-2 cells that model the human intestine found that exposure to AZA-1 interfered with the protein occludin, and leading to disruption in paracellular permeability (Abal et al, 2017). A further observation of AZA-1 exposure to Caco-2 cells was a disorganisation of actin cytoskeleton and a decrease in adherence, this could be a factor involved in increased intestinal permeability (Vilariño et al, 2006, Vilariño, 2008.…”
Section: Figure 12mentioning
confidence: 99%